Treatment Outcomes of Tocilizumab in Critically-Ill COVID-19 Patients, Single-Centre Retrospective Study - Wael Hafez; Mohamad Azzam Ziade; Arun Arya; Husam Saleh; Mahmoud Abdelshakor; Osman Fadl Alla; Pragati Agrawal; Sara Ali; Srinivasa Raghu Rao; Subrata Gupta; Ikram Abdelli; Honeymol Sebastian; et al. (MDPI AG, 2022)
(1) Background: Severe COVID-19 outcomes are associated with cytokine release syndrome, characterized by the release of several immune modulators, including Interleukin-6 (IL-6). Tocilizumab (TCZ) is an IL-6 receptor antagonist used to treat rheumatic arthritis. The study aimed to evaluate the efficacy and safety of TCZ against COVID-19. (2) Methods: This was a retrospective study including 49 severe COVID-19 patients who received TCZ therapy in NMC Royal Hospital, UAE. (3) Results: Before Tocilizumab administration, the median temperature was 37.0 (IQR 36.0-39.6), and after day seven, the median reduced to 36.5 (IQR 35.8-37.9), p > 0.001. Thirty (61.2%) patients were admitted to the ICU, of which, eight (16.3%) were on WHO scale 4, sixteen (32.6%) on scale 5, and six (20.0%) on scale 6. TCZ reduced inflammatory markers over time, including CRP, D-Dimer, Ferritin, and Fibrinogen. By the end of week seven, 14 patients died (28.6%) while 35 (71.4%) improved and were discharged. (4) Conclusions: The study showed limited improvements in COVID-19 outcomes with TCZ therapy and highlighted the importance of D-Dimer monitoring for possible risk of thrombosis. Additionally, it could be recommended to upgrade the anti-coagulation dose to therapeutic levels once TCZ therapy is decided upon.